Pengaruh Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Frozen Food (Studi Kasus Produk Sosis Belfoods Pada Konsumen Di Gucci Frozen Food Cikarang) - Indra Sumarna Sobari; Asra Maulida Farhah (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study was carried out at the Gucci Frozen Food Cikarang store, with the aim of determining the extent to which price (X1) and product quality (X2) affect the purchase decision (Y). The sampling technique used was purposeful sampling from 96 respondents. The method used is a quantitative method, while the test steps are validity, reliability, multiple linear regression analysis, hypothesis testing and coefficient of determination using SPSS 26 software. on a Windows computer system.Based on data analysis, the results of multiple linear regression analysis are Y = 17,719 + 0.578 X1 + 0.141 X2 + e, which shows if the price variable (X1) and the product quality variable (X2) are considered to be zero. change, the decision purchase (Y) will be positive and meaningful. Based on the F test, it is known that the calculated F value is 68,427, this figure shows that the calculated F value is larger than the table F, so Ho is rejected and Ha is accepted. Thus, the variables of price and product quality simultaneously affect the purchasing decision. This shows that there is an influence of price and product quality on purchasing decisions. Based on t-test, the results show that price has a positive effect on purchasing decision with t-value of 6,910 > panel t-value of 1,986 and significance level of 0.000 <0> panel t-value of 1,986 and a significance level 0.002 < 0; 0.05, it can be concluded that price and product quality changes have a significant influence on purchasing decisions. An R-squared value of 0.595 indicates that the contribution of the independent variable, i.e. price and product quality, to the dependent variable, i.e. purchase decision in the study, is 59.5% of the variable. dependent, namely purchase decision, while the rest 40.5% (100% - 40.5%) is influenced by other factors that have not been considered in this study.